Financing Of Teck's Investment In The Bullmoose Coal Project - N. R. MacMillan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
INTRODUCTION The Bullmoose Coal Project is part of a major development in northeastern British Columbia which comprises a new rail line, a new townsite, powerline, highway, the upgrading of the Canadian National Railway's main line, a new coal port at Prince Rupert and two new coal mines, the Bullmoose mine and the Quintette mine. The total investment by all parties is estimated to be in excess of $2.6 billion and made up approximately as follows : [Table No. 1 $ Millions - Quintette Coal Limited 950 Teck-Bullmoose Coal Inc. 275 Canadian National Railway Company 800 6 British Columbia Railway Company Port at Prince Rupert 280 Townsite, Roads 6- Power ] The new infrastructure is intended to serve not only the Bullmoose and Quintette coal projects but also eventually a number of other coal properties in northeastern British Columbia. The Bullmoose project is structured on a joint venture basis as follows : [Table No. 2 Teck Corporation 51% Lornex Mining Corporation Ltd. 39% Nissho Iwai Coal Development 1 0% (Canada) Ltd. -- 100% ] The mine has a capacity of 2.3 million tonnes of clean coal per year. In the initial years 1.7 million tonnes will be metallurgical coal and 0.6 million tonnes thermal coal. After the first three years of operations the annual production of metallurgical coal will increase to an average of approximately 2.1 million tonnes and the production of thermal coal will decrease to an average of approximately 0.2 million tonnes. At this level of 2.3 million tonnes annual production, the Bullmoose mine has sufficient reserves for at least 26 years of production. History Brameda Resources Ltd. commenced coal exploration in the Bullmoose-Sukunka area in 1969. Teck obtained an option on the Bullmoose coal licences in 1970 and started surface exploration and diamond drilling in 1971. Teck earned a 50% interest in the property, and thereafter expenses were jointly financed by Teck and Brameda. In 1981 Brameda merged with Teck making Teck the sole owner. The initial phase of the exploration program, which was completed in 1975, included 7,200 meters of diamond drilling in 35 holes. During 1976 and 1977, detailed exploration and test work were carried out on the South Fork and West Fork areas where multiple seams close to surfaces indicated the potential for large tonnages of strippable coal. In those two years, work included road construction, detailed mapping and trenching to outline the coal seam traces at the surface, 6,300 meters of diamond drilling in 80 holes, and 300 meters of underground bulk sampling from seven adits. Washability tests and analysis work were carried out on the drill cores and adit samples, and pilot plant washability studies were undertaken. In 1978 and 1979 Teck engineers prepared open pit mining plans and production schedules and Kaiser Engineering was retained to prepare a layout of the plant preparation facility. A feasibility study prepared by Teck's engineering group in January 1982 was the base document used by the Lenders in assessing the technical and economic viability of the project. Property Location The property lies some 650 kilometers northeast of Vancouver, and 87 kilometers south by road from the village of Chetwynd. The Sukunka property (British Petroleum) adjoins to the north, the Mount Spieker property (Ranger Oil Option) adjoins to the east, and the Quintette property is located to the southeast.